Novel single nucleotide polymorphism in the prolactin gene of Awassi ewes and its role in the reproductive traits - al-Thuwayni, Tahrir Muhammad (Iraqi journal of veterinary sciences, 2021)
أجريت هذه الدراسة لتحديد الاختلاف الجيني لجين البرولاكتين PRL في منطقة المحيطة من طرف 5 و علاقتها مع العديد من الصفات التكاثرية في الأغنام العواسية. تضمنت هذه الدراسة 106 نعاج عواسية عراقية ناضجة جنسيا و صحية تراوحت أعمارهم بين 2 إلى 2.5 سنة. تم تصنيف النعاج إلى قسمين رئيسيين؛ النعاج التي تنتج التوائم و النعاج التي تنتج ولادة مفردة. لوحظ طرازان وراثيان AA و AT في الأغنام العواسية. بينما تم الكشف عن الطراز الوراثي AA في النعاج العواسية التي أنتجت توائم، كشف عن الطراز الوراثي AT في النعاج التي أنتجت نسلا مفردا. حددت تفاعلات التسلسل الجيني تسعة طفرات نوع التباين الوراثي للنيوكليوتيدات المفردة في جين البرولاكتين عند المنطقة المحيطة من طرف 5 ′ في الأغنام العواسية، تختلف عن تسلسل البرولاكتين المرجعي GenBank X16641.1. يمتلك الطراز الوراثي AT طفرة واحدة بديلة التباين الوراثي للنيوكليوتيدة المفردة مقارنة مع الطراز الوراثي AA في النعاج العواسية. كشف تحليل الارتباط أن الطراز الوراثي AA يتميز بمستويات أعلى بكثير من تركيز البروجسترون، نسبة التوأئم، الخصب، و الخصوبة من الطراز الوراثي AT. في الاستنتاج، تم اكتشاف طفرة جديد (g.1209 A>T) داخل منطقة المحيطة بالجين للأغنام مما قد تؤثر على التعبير الجيني للبرولاكتين، كما أظهرت هذه النتائج أن الطراز الوراثي AA مرتبط بالخصوبة العالية للأغنام العواسية و الذي يمكن استخدامه كمعيار اختيار لتحسين الأداء التناسلي للأغنام العواسية العراقية. This study was conducted to determine the genetic variation of the prolactin (PRL) gene in 5' ﬂanking region and its role with several reproductive traits in Awassi sheep. One-hundred six Iraqi sexually mature and healthy Awassi ewes that aged between 2 and 2.5 years were included in this study. Ewes were classified into two the main divisions: ewes producing twins and ewes producing single offspring. Two genotypes (AA and AT) were observed in Awassi sheep. While genotype AA was detected in Awassi ewes that produced twins, genotype AT was detected in ewes that produced a single offspring. The sequencing reactions identified nine SNPs in the prolactin gene at the 5′ flanking region in Awassi sheep, differing from the prolactin reference sequence (GenBank accession number X16641.1). Genotype AT possessed one single nucleotide polymorphism SNP substitute comparison with the AA genotype in Awassi ewes. The association analysis revealed that the AA genotype is characterized by significantly higher levels of the progesterone concentration, twinning ratio, fecundity, and prolificacy than the AT genotype. In conclusion, a new SNP (g.1209 A>T) was discovered within the ovine flanking region which potentially influences prolactin gene expression. These results showed that the genotype AA associated with high prolificacy of Awassi sheep may be used as a selection criterion for improving the reproductive performance of Iraqi Awassi sheep.